Pengaruh Penerapan Model Problem Based Learning Terhadap Hasil Belajar Siswa Subtema Kebersamaan dalam Keberagaman - Derika Septiani Rachmat; Nedin Badruzzaman; Nurlinda Safitri (STKIP Andi Matappa Pangkep, 2023)
This study used a quasi-experimental approach with a two-group design at Cileungsi 06 State School. The subjects of the study were IV A and IV B Cileungsi 06 State Elementary School which were conducted in the odd semester of the 2022/2023 academic year. The results of the study are the influence of learning outcomes on the sub-theme of togetherness in diversity in class IV at SDN Cileungsi 06, Bogor Regency using the Problem Based Learning model with an N-Gain score of 60 and an average pretest score of 56, an average posttest score of 84 and the percentage of completeness learning outcomes of 94% while the acquisition of learning outcomes using the conventional model is the N-Gain value of 55 and the pretest average value is 50, the posttest average value is 75 and the percentage of complete learning outcomes is 70%. The results of testing the hypothesis, namely the alternative hypothesis (Ha) is accepted because tcount (5.13016) is greater than ttable (2.00030). So it can be concluded that there is a significant influence on the application of the learning model in the classroom, especially the problem based learning model on the Togetherness in Diversity sub-theme.